Correlation between framingham risk score and cardiometabolic risk profile in Malaysian obese adults - Shahadan, Siti Zuhaidah; Daud, Azlina; Ibrahim, Muhammad; Md Isa, Muhammad Lokman; Draman, Samsul (2016)
Introduction: Obese adults have increased risk of developing cardiovascular diseases (CVD), which can be estimated using Framingham risk score (FRS). Identifying the risk of developing CVD may reiterate the necessity of intensive intervention to reduce the ever-increasing burden of this disease. However, national data of FRS and its relationship with cardiometabolic risk (CMR) profile among Malaysian obese adults are insufficient. Objectives: The study was aimed to determine the prevalence of CMR profile and its relationship with FRS in Malaysian obese adults. Methods: A total of seventy one obese adults from Kuantan community (body mass index (BMI) ranged between 27.5 kg/m2 to 40 kg/m2 and age ranged between 20 to 62 years) were selected. Assessment of BMI, waist circumference (WC), blood pressure (BP), lipid profile and fasting blood glucose (FBG) were conducted. FRS was calculated using the online CVD risk calculator from National Institutes of Health (NIH) website. The variables used to estimate the risk were age, gender, BMI, systolic BP, smoking status, total cholesterol and high density lipoprotein (HDL), and hypertensive treatment. Results: For CMR abnormalities, the results show that WC (cm) and total cholesterol level (mmol/L) were elevated in both genders (WC: male; 101.78±8.63, female; 93.86±6.92, and total cholesterol: male; 5.63±0.73, female; 5.28±0.92). All participants in this study have low risk of developing CVD in the next 10 years (<10%) based on the FRS points. Male have higher FRS points as compared to female (p<0.05, CI 95% 0.31 to 3.17). Pearson correlation shows a moderate strength, positive linear relationship between FRS points and FBG level in both genders (male; r=.492, p=.003, n=20, female; r=.545, p<0.001, n=51). Discussion: Our result showed that obesity induced impaired fasting glucose was a significant factor in developing CVD among obese adults with elevated WC and total cholesterol level. It proves the theory that expanded adipose tissue in obese adults has increased blood glucose concentration. Conclusion: The present findings showed that Malaysian obese class I and II adults have elevated WC and total cholesterol level, and FBG was significantly correlated with FRS.